Types of English Intensifiers on Social Media - Suryaningsih, Yuli; Hardjanto, Tofan Dwi (Language Circle: Journal of Language and Literature, 2021)
The use of English intensifiers keeps changing and flowing. It also varies according to the speaker’s background and style. Quirk, et.al (1992) divides intensifiers into emphasizers, amplifiers (maximizers, boosters), and downtoners (approximators, compromisers, diminishers, minimizers). This research aims to find out the types of English intensifiers on social media, specifically on Twitter. The most frequently used intensifiers are analyzed specifically to dig deeper into the social aspects in terms of the relation with previous studies. There are 8,975 tweets produced by 23 sample users. The data are clear data, which means that they only consist of English tweets, without replies and retweets. From the 8,975 tweets, there are 194,487 word-tokens and 22,877 word-types. In the data, 92 intensifiers are used 1,633 times. The occurrence of intensifiers consists of 153 emphasizers, 480 maximizers, 891 boosters, 11 approximators, 38 compromisers, 46 diminishers, and 14 minimizers. This study reveals that the most used intensifier on Twitter is so. The use of so is quite popular since Tagliamonte & Roberts (2005) also found in their study that the use of ‘so’ and ‘very’ were the most frequently used. Besides, this study also corresponds to Setayesh and Vaez-Dalili (2018) that boosters are the most frequently used.